Răspuns :
M.G= [tex] \sqrt{ax b} [/tex]
calculam prima data " a x b"
(2-√3)²( 2+√3)²= (4-4√3+3)(4+4√3+3)
=16+16√3+12-16√3-48-12√3+12+12√3+9
=16+12-48+12+9
=1
M.G= [tex] \sqrt{axb} = \sqrt{1} =1[/tex]
calculam prima data " a x b"
(2-√3)²( 2+√3)²= (4-4√3+3)(4+4√3+3)
=16+16√3+12-16√3-48-12√3+12+12√3+9
=16+12-48+12+9
=1
M.G= [tex] \sqrt{axb} = \sqrt{1} =1[/tex]
[tex] Mg = \sqrt{ab}= \sqrt{ (x- \sqrt{3} )^{2} (x+ \sqrt{3} )^{2}} = [/tex]
[tex]= \sqrt{ [(2- \sqrt{3})(2+ \sqrt{3} )]^{2}} = (2- \sqrt{3})(2+ \sqrt{3}) = 4 - 3 = 1[/tex]
[tex]= \sqrt{ [(2- \sqrt{3})(2+ \sqrt{3} )]^{2}} = (2- \sqrt{3})(2+ \sqrt{3}) = 4 - 3 = 1[/tex]